Analisis subsidi bahan bakar minyak (BBM) solar bagi nelayan di Kabupaten Aceh Besar, Provinsi Aceh - Zainal A. Muchlisin; Nur Fadli; Arifsyah M. Nasution; Rika Astuti Rika Astuti; Marzuki M (Depik, 2012)
Abstract. Fuel is one of important components in fishing activity. The objectives of this research were to analyze the need and the receiver of fuel subsidy in Aceh Besar t as well as to analyze the problems that faced by fisherman in Aceh Besar district. The survey was done on June-August 2012 in five sub-district in Aceh Besar namely: (1) Baitussalam, (2) Mesjid Raya, (3) Leupung (4) Lhoknga dan (5) Mesjid Raya. The result shown that the average cost of one trip of fishing activities in Aceh Besar were Rp700.000. The lowest operational cost was found in Seulimum (Rp96.200 per trip) and the highest was found in Baitussalam sub-district (Rp1, 793,710 per trip). Fuel was the biggest cost for fishing activity; it was ranged 40%-73% with average 57.9%. The lowest proportion of fuel consumption was found in Baitussalam sub-district and the highest was found in Lhoknga sub-district. In average, the fisherman’s fuel consumption was 1,237L. per month; with total subsidy was Rp 5,824,737 per fisherman per month. The profit will be decreased up to 89.5% if there was no fuel subsidy. In addition, the result also shown that the fisherman in Aceh Besar did not have any skill to generate their alternative income. As the consequence, in the future there is a need to develop programs to generate the alternative livelihood for Aceh Besar fisherman as well as their family.Keywords. Capture fishery, conservation, budget allocation, and climate changes